Study on the Calculation of Mesh Stiffness and Longitudinal Load Distribution of Spur Gear with the Lead Crown Modification - Xing Bin; Hou Mingxi; Kong Xiangfeng (Jixie chuandong)
The Longitudinal modification technology has been the most promising method to improve transmission performance and suppress vibration and noise. The mesh stiffness and longitudinal load distribution are primary parameters to evaluate the effect of modification. By using the finite element quasi-static analysis principle,the mesh stiffness and longitudinal load distribution of modification gears in the different modifications are calculated quantitatively according to the influence of installation errors. The effects of tooth profile correction amount and installation errors on mesh stiffness and longitudinal load distribution analysis are obtained. These analysis results show that the mesh stiffness is increased and the longitudinal load distribution caused by the shaft nonparallelsm is reduced. Meanwhile,at a given installation errors,there is the best range of the tooth profile correction amount,when deviating this range,the transmission performance goes worse.